Présent rétrospectif et détour post-humain chez Clifford Simak et Michel Houellebecq - Juliette Feyel (ReS Futurae)
This article draws a comparison between City by Clifford Simak and The Possibility of an Island by Michel Houellebecq. Both novels demonstrate the same kind of narratological device: our time (1950-2005) is portrayed by a narrating voice from beyond humankind’s extinction. The paper interrogates both novelists’ depiction of future times from a posthumanist perspective and reaches the conclusion that Simak appears to hold more antihumanistic views than Houellebecq.